(Table 1, page 381) Chemical composition of metalliferous sediments from DOMES Site C, Pacific Ocean - James L Bischoff; Robert J Rosenbauer (PANGAEA, 1977)
Quaternary sediments cored in the northeast Pacific nodule area (DOMES site C, 14°N, 126°W) contain a significant amount of hydrothermal metalliferous mud. Water content, color, mineralogy, and chemical composition are analogous to metalliferous sediments of the subequatorial East Pacific Rise. Correction for contribution of pelagic clay indicates the metalliferous fraction to be about 40% of the sediment. SiO2 and Mg are major components in the corrected composition, as they are for other metalliferous sediments similarly corrected from a variety of East Pacific Rise and DSDP metalliferous sediments. A correlation between Mg and SiO2 for these corrected sediments could indicate a hydrothermal origin for a significant portion of the SiO2. Results from DSDP in the nodule area suggest that metalliferous globules are a ubiquitous minor component of the Clipperton Oceanic Formation, which underlies much of the Pacific ferromanganese nodule belt. This indicates that deposition of hydrothermal precipitates is not confined to spreading centers.
Supplement to: Bischoff, JL; Rosenbauer, RJ (1977): Recent metalliferous sediment in the North Pacific manganese nodule area. Earth and Planetary Science Letters, 33(3), 379-388, https://doi.org/10.1016/0012-821X(77)90089-9